Xanthohumol Attenuated Inflammation and ECM Degradation by Mediating HO-1/C/EBPβ Pathway in Osteoarthritis Chondrocytes - Zhang, Ming; Zhang, Rui; Zheng, Tiansheng; Chen, Zhixi; Ji, Guanglin; Peng, Fang; Wang, Wei (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is the most frequent and disabling disease in developed countries. The progressive degeneration of articular cartilage characterized as thinner and erosive. Inflammation is well-known to be involved in OA development. However, there are no effective therapeutic strategies to cure it. Xanthohumol (XH) is a natural prenylflavonoid isolated from hops and beer. The protective activity of XH against OA chondrocytes inflammation and ECM degradation is unclear. In this article, we found that XH significantly inhibited inflammatory responses, attenuated catabolic enzymes expression, and ameliorated ECM degradation, as showed by decreased production of NO, PGE2, TNFα, and IL-6, decreased expression of MMP-3/-13 and ADAMTS-4/-5, and increased expression of collagen-II and aggrecan. In addition, XH activated HO-1 signaling and attenuated IL-1β-induced C/EBPβ. XH promoted the interaction between HO-1 and C/EBPβ, inhibiting the nuclear translocation of C/EBPβ. HO-1 knockdown could abrogate the protective effects of XH in IL-1β-treated chondrocytes. Collectively, XH attenuated inflammatory responses and ECM degradation by mediating HO-1 and C/EBPβ signaling pathways in osteoarthritis chondrocytes.